Waveform and frequency effects on corrosion-fatigue crack growth behaviour in modern marine steels - Igwemezie, Victor C.; Mehmanparast, Ali (Elsevier, 2020)
The primary focus of this work is to investigate the sensitivity of cyclic waveform, frequency (f), load level and microstructure on the corrosion-fatigue crack growth rate (CFCGR) in modern normalised-rolled (NR) and thermomechanical control process (TMCP) ferrite-pearlite steels in the Paris Region of the da/dN vs. ΔK log-log plot. Constant amplitude sinewave (si) and trapezoid waveform (generally referred to here as hold-time (h-t)) were used under frequencies of 0.2 Hz, 0.3 Hz and 0.5 Hz and stress ratio of 0.1. Comparison is also made between the crack path in the S355 TMCP steel under si and h-t in seawater (SW). The role of microstructure in retarding or accelerating fatigue crack growth in SW is also discussed. Experimental results showed that the CFCGR corresponding to the si is higher than that of the h-t for all the load levels and frequencies examined. It was observed that reduction in the f and fatigue load level increased the CFCGR for the h-t but had little effect on the si. Generally, f in the range 0.2–0.5 Hz had little effect; and for a given f an increase in load led to a reduction in the CFCGR, in the Paris Region (PR) for both si and h-t in SW. Under both si and h-t, the CFCGR in the TMCP steels (e.g. S355G8 + M, S355G10 + M) is lower than that of the normalised steels (e.g. S355J2 + N). Metallurgical analyses on the fractured surface of corrosion-fatigue specimens show that the main active crack tip blunting process is the primary factor controlling the CFCGR of steel at high stress intensity factor range (SIFR) and low f in SW. The results obtained from this study have been discussed in terms of the potential impact on the structural design and integrity of offshore wind turbine foundations.
Keywords: S355 steel; Corrosion-fatigue; Sinewave; Hold-time; Seawater; Microstructure